Pushing the boundaries: a physical activity intervention extends sensor-assessed life-space in nursing home residents - Jansen, Carl-Philipp; Schilling, Oliver; Werner, Christian; Wahl, Hans-Werner; Hauer, Klaus (The gerontologist, 2018)
Background and Objectives: To determine whether a multicomponent, individually tailored intervention to promote physical activity (PA) enhances life-space (LS) utilization in nursing home (NH) residents and whether intervention effects can be sustained at follow-up after continuation of the program as part of institutional daily routines. Research Design and Methods: Pre-post-assessed controlled trial in two highly similar NHs with a 3month follow-up in 143 NH residents (intervention group: n = 78; control group: n = 65) and LS as primary outcome. The PA promoting intervention consisted of several components (group sessions; individual exercise; serious games training; competence training for staff) tailored to residents’ individual functional capacity. LS was innovatively assessed via an indoor wireless sensor network including three assessment-specific LS parameters: overall LS score (LSSc), time spent away from the private room (TAFR), and the maximally distal zone from private room visited (MaxZ). To exploit the available intervention-control comparative data in the best way possible, a generalized linear mixed model approach was applied. Results: At post-test, intervention participants had a significantly higher overall LSSc, spent more TAFR, and had extended their MaxZ as compared to controls. At follow-up, a significant group difference remained for MaxZ. Discussion and Implications: A PA intervention in the NH setting impacts on LS utilization as measured using sensor-based assessment. The program has proven its practical sustainability when being handed over to NH personnel for continuation in daily practice. Further research is needed to determine whether an increase in LS utilization also impacts on social participation and quality of life.
Gesehen am 21.11.2018
Advance access publication: September 15, 2017